1.1 DIASTOLIC LEFT VENTRICULAR FUNCTION IN RELATION TO CIRCULATING METABOLIC BIOMARKERS IN A GENERAL POPULATION - Zhen Yu Zhang*; Vannina Marrachelli; Lutgarde Thijs; Wen Yi Yang; Fang Fei Wei; Daniel Monleon; Lotte Jacobs; Tim Nawrot; Peter Verhamme; Jens-Uwe Voigt; Tatiana Kuznetsova; Josep Redón; et al. (Artery Research, 2015)
Background: The metabolic signature associated with subclinical diastolic left ventricular (LV) dysfunction in the general population is unknown. Objectives: This population study aimed at identifying a specific profile of circulating me-tabolites associated with asymptomatic diastolic LV dysfunction. Methods: In 711 randomly recruited Flemish (50.8% women; mean age, 50.8 years), we assessed echocardiographic indexes of diastolic LV function in relation to 44 circulating metabolites determined by nuclear magnetic resonance spectroscopy. Statistical methods included multivariable-adjusted regression analyses and partial least square discriminant analysis (PLS DA). Results: In multivariable analyses with Bonferroni correction, a′ was inversely and e′/a′ was positively correlated (p ≤ 0.048) with circulating tyrosine, HDL apolipoproteins, glucose + glutamine, and an unidentified molecule, while a′ was also inversely associated with glucose + 2 aminobutyrate and glucose + 2 phosphoglycerate (p ≤ 0.031). PLS-DA identified three latent factors accounting for 54.4% of the variance. The metabolites associated with better diastolic LV function included, amongst others, glucose + glutamine (variable importance in projection score, 1.201), glucose + 2 aminobutyrate (1.185), and glucose + 2 phosphoglycerate (1.172). The three latent factors, compared with N-terminal prohormone brain natriuretic peptide, increased (p < 0.0001) the area under the curve from 0.64 to 0.73. Conclusions: In the general population, diastolic LV function is associated with a profile of circulating metabolites indicative of energy substrate utilization and protection against oxidative stress. These metabolic markers might lead to the discovery of new targets for prevention and treatment of diastolic LV dysfunction at a subclinical and still reversible stage.